Community resilience during typhoon Ondoy the case of Ateneoville - Adviento, Maria Luisa G.; de Guzman, Judith M. (Philippine journal of psychology, 2010)
"This research looked into the experiences of survivors in the wake of typhoon Ondoy. Using positive psychology as a framework for understanding community survival and resilience in disaster situations, we examined the positive characteristics among members of a community that was severely affected by the typhoon. Based on focus group discussions, ten positive characteristics were identified as both resources and outcomes in the disaster experience. These were: 1. Pakikibagay sa kalikasan, 2. Malasakit, 3. Bayanihan, 4. Tiwala, 5. Pagtitiis, 6. Pagkmasayahin at palabiro, 7. Lakas ng loob at tapang sa gitna ng takot 8. Pagkamaparaan, 9. Pasasalamat, and 10. Pananalig sa Diyos."